Gastrointestinal parasites in rural dogs and cats in Selangor and Pahang states in Peninsular Malaysia - Romano, Ngui; Soo, Ching Lee; Nan, Jiun Yap; Tiong, Kai Tan; Roslan, Muhammad Aidil; Kek, Heng Chua; Shafie, Aziz; Wan Yusoff, Wan Sulaiman; Arine Fadzlun, Ahmad; Rohela, Mahmud; Yvonne Ai, Lian Lim (Witold Stefański Institute of Parasitology, Polish Academy of Sciences, 2014)
To estimate the current prevalence of gastrointestinal (GI) parasites in dogs and cats, a total of 105 fresh faecal samples were collected from rural areas in Peninsular Malaysia. Each faecal sample was examined for the presence of GI parasites by microscopic examination after formalin-ether concentration technique and for protozoa, trichrome and Ziehl-Neelsen staining were employed. The overall prevalence of GI parasitic infection was 88.6% (95% CI = 82.5–94.7) in which 88.3% of dogs and 89.3% of cats were infected with at least one parasites species, respectively. There were 14 different GI parasites species (nematodes, cestodes and protozoa) detected, including Ancylostoma spp. (62.9%), Toxocara spp. (32.4%), Trichuris vulpis (21.0%), Spirometra spp. (9.5%), Toxascaris leonina (5.7%), Dipylidium caninum (4.8%), Ascaris spp. (2.9%), Hymenolepis diminuta (1.0%) and others. General prevalence of GI parasites showed a significant difference between helminth (84.4%) and protozoa (34.3%) infections. Monoparasitism (38.1%) was less frequent than polyparasitism (46.7%). As several of these GI parasites are recognized as zoonotic agents, the results of this investigation revealed that local populations may be exposed to a broad spectrum of zoonotic agents by means of environmental contamination with dogs and cats faeces and this information should be used to mitigate public health risks. Prevention and control measures have to be taken in order to reduce the prevalence rates especially in socioeconomically disadvantaged communities where animals live in close proximity to people, poor levels of hygiene and overcrowding together with a lack in veterinary attention and zoonotic awareness.